YIELD AND QUALITY IMPROVEMENT OF SUNFLOWER (H ELIANTHUS ANNUUS L.) HYBRID THROUGH ABA APPLICATION UNDER WATER DEFICIT CONDITIONS - S. Hussain; M. F. Saleem; A. Ali; J. Iqbal; M. A. Shakir (Journal of Animal and Plant Sciences, 2013)
Abscisic acid (ABA) application helps in improving sunflower oil quality and yield through ameliorating the adverse effects of limited water supply at different growth stages of sunflower hybrid. Improvement in yield and quality of sunflower hybrid by exogenous application of ABA under drought was studied through field experiment executed at the Agronomic Research Farm, University of Agriculture, Faisalabad, Pakistan. Three irrigation schedules i.e. four irrigations (25 DAS, bud initiation, flower initiation and achene formation), three irrigations (25 DAS, flower initiation and achene formation) and three irrigations (25 DAS, bud initiation, and achene formation) were used. Sunflower hybrid hysun-33 was exposed to ABA concentrations (0, 5µm and 10µm) at bud initiation or at flower initiation. ABA application to sunflower hybrids either at bud or at flower initiation under water deficit conditions improved achene oil content, yield and decreased achene protein contents. Drought stress and ABA application exhibited inverse results for oil quality and yield. Drought stress to sunflower hybrid at bud or at flower initiation increased stearic and oleic acid and decreased palmitic and linoleic acid while exogenous application of ABA under water deficit at both stages slightly decreased stearic and oleic acid but increased palmitic and linoleic acid. It was concluded that exogenous application of ABA to sunflower under drought improved quality and increased crop yield.
Keywords: Water deficits; abscisic acid; hybrid sunflower; oil quality and yield